PENGARUH SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP VITAL SIGN PADA PASIEN GAGAL GINJAL - Rizky Nur Evinda; Susi Milwati; Atti Yudiernawati (Poltekkes Kemenkes Malang, 2019)
Abstract: The purpose of this study was to determine the influence of spiritual emotional freedom tehnique (SEFT) to the vital sign in patients with renal failure in RSUD Ngudi Waluyo. The design of this research is quasi experiment with time series design. The population was all patients with renal failure in RSUD Ngudi Waluyo, while the sample was a part of the population that fulfilled the inclusion criteria of 29 respondents. The sampling technique used is non probability sampling with purposive sampling specification. Technique of collecting data with measurement of vital sign before and after given treatment. Processing and data analysis used in this research is with Wilcoxon Test. The result of data analysis shows that there is influence of spiritual emotional freedom technique (SEFT) to vital sign in patients with renal failure in RSUD Ngudi Waluyo, with p is 0,000. Keywords: SEFT, vital sign, kidney failure patient